2017
DOI: 10.1080/14767058.2017.1408069
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract injuries during cesarean section in patients with morbid placental adherence: retrospective cohort study

Abstract: The morbid adherent placenta is still a challenge, which faces us as obstetricians, due to high morbidity and mortality. A multidisciplinary team is mandatory to avoid complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…Bladder injury was recorded in 39.5%. Our findings were supported by many studies which reported that complications after cesarean hysterectomy were higher with bladder and ureteric injuries are the most common injuries reported [26, 3336].…”
Section: Discussionsupporting
confidence: 89%
“…Bladder injury was recorded in 39.5%. Our findings were supported by many studies which reported that complications after cesarean hysterectomy were higher with bladder and ureteric injuries are the most common injuries reported [26, 3336].…”
Section: Discussionsupporting
confidence: 89%
“…Also authors reported one case (0.2%) of colonic injury and 2 cases (0.4%) of vascular injury that is in agreement with Rosenberg et al 2011 study who reported that surgical complications such as cystotomy, ureteric and vascular injury are more with PA. 11 Additionally, these results were coincided with Alanwar et al, 2018 who reported the incidence of urinary tract injuries during CS with morbid adherence placenta was 21.7% (Bladder 11.7%, Ureter 4.7%, and bladder with ureter 5.3%). 12 In rare cases, the placenta could invade beyond the abdominal viscera and reach the anterior abdominal wall. 13 In the present study, the placenta left in situ in 3 cases of PA. All cases needed blood transfusions (up to 10 units) and one of them ended by post-operative uterine sepsis and ended by hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study [4] reported that, patients with repeated Cesarean sections were associated with bladder injury in 0.81% of cases while bladder injury was reported only in 0.27% of patients who had Cesarean section for first time. Urinary bladder injury complicates about 11.7% of cesarean sections in women with placenta accreta spectrum (PAS) [5]. Urinary bladder adhesions are the main risk factor for urinary bladder injury.…”
Section: Introductionmentioning
confidence: 99%